Integrative bioinformatic and experimental analysis reveals prognostic and immunological roles of MEX3 family genes in glioma - Zhang, Xuezhong; Shang, Hui; Chu, Tingting; Sha, Kaihui (Frontiers in Immunology, 2026)
BackgroundGlioma is a highly heterogeneous and aggressive malignancy of the central nervous system, and reliable molecular biomarkers are urgently needed to improve prognostic stratification and guide therapeutic decision-making. The MEX3 family of RNA-binding proteins has been implicated in tumorigenesis and post-transcriptional regulation; however, their comprehensive roles in glioma remain poorly understood.MethodsIntegrated bioinformatic analyses were performed using transcriptomic and clinical data from TCGA, CGGA, and GEO cohorts to evaluate the expression profiles, diagnostic and prognostic value, genetic alterations, molecular interactions, immune infiltration characteristics, and functional pathways associated with MEX3A, MEX3B, MEX3C, and MEX3D. Protein-protein interaction networks, gene set enrichment, and co-expression analyses were conducted to explore potential biological mechanisms. A MEX3-related prognostic risk model was constructed and validated in independent datasets. Drug sensitivity correlations were analyzed using public pharmacogenomic resources. In addition, in vitro experiments, including qRT-PCR, western blotting, proliferation, migration, and invasion assays, were performed in U251 and LN229 glioma cell lines to functionally validate the bioinformatic findings.ResultsAll four MEX3 family members were significantly upregulated in glioma tissues compared with normal controls and demonstrated strong diagnostic performance. Distinct prognostic patterns were observed, with MEX3D consistently identified as an independent predictor of poor overall, disease-specific, and progression-free survival. MEX3 genes were associated with diverse genetic alterations and were enriched in pathways related to RNA processing, cell cycle regulation, and cancer-associated signaling. Immune analyses revealed significant correlations between MEX3 expression and multiple immune cell populations as well as immune checkpoint molecules, suggesting potential roles in shaping the glioma immune microenvironment. A MEX3-related co-expression-based prognostic model showed robust survival-predictive ability and remained effective in external validation cohorts. Functional assays confirmed that silencing individual MEX3 genes significantly inhibited glioma cell proliferation, migration, and invasion in vitro.ConclusionsThis study provides a comprehensive characterization of the MEX3 family in glioma, demonstrating their dysregulation, prognostic relevance, immune associations, and functional contributions to malignant phenotypes. Among them, MEX3D emerges as a particularly promising prognostic biomarker. These findings establish a foundation for future mechanistic and translational studies exploring MEX3 family members as potential biomarkers or therapeutic targets in glioma.